The Influence of Facilities Maintenance, Service Quality and Work Culture on Inpatient Satisfaction at Medika Dramaga Hospital, Bogor - Kurniasari, Ludfia; Djamil, Masyhudzulhak; Suherman, Suherman (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research is about the satisfaction of inpatients at Medika Dramaga Hospital which explores patient statements regarding the facilities, service quality and staff work culture. The method used is descriptive research with a quantitative approach. The sample is from 100 patients or families of inpatients as respondents using data collection techniques through questionnaires and hypothesis analysis using SEM-PLS. Data processing in this study has shown that all hypotheses are accepted, with details based on the Path coefficient value, it is known that the T - statistical value of Facility Maintenance on Patient Satisfaction is 8.772 so that T - Statistics > t-table (1.96 ), from these results it can be stated that Facility Maintenance has a positive effect on patient satisfaction. The Path coefficient value shows that the T - statistical value of Service Quality on Patient Satisfaction is 2.122 so that T - Statistics > t-table (1.96), from these results it can be stated that Service Quality has a positive effect on Patient Satisfaction. And the Path coefficient value shows that the T - statistical value of Work Culture on Patient Satisfaction is 2.943 so that T - Statistics > t-table (1.96), from these results it can be stated that Work Culture has a positive effect on Patient Satisfaction . Keywords : Facility Maintenance, Service Quality, Work Culture, Patient Satisfaction